Traveling through violence - Grgurinović, Ivona (2013)
This paper deals with multiple connections between travel and violence, from the “violences underlying all travel” (John Hutnyk) in general, to gendered connections between travel and violence, and specific traveling through violence by a woman travel writer, Dervla Murphy. The Western discourse of travel has historically been marked by a range of “European, literary, male, bourgeois, scientific, heroic, recreational, meanings and practices” (James Clifford), signifying a closed and defined type of experience, mainly excluding those diverging from it in terms of gender, race, class, etc., but also being largely enabled by a history of (colonial) violence. Women, apart from being intruders in these predominantly male histories of travel, also, even after they begin to travel more extensively, as solitary travelers always travel with a threat of physical violence. Dervla Murphy, a well-travelled Irish travel writer, although often assuming the role of an “honorary man” (Debbie Lisle), has, on the one hand, often in the course of her many travels, been exposed to violence as a solitary woman traveller, but has also often traveled through violent regions in critical moments in history (e.g. South Africa) or witnessed the aftermath of violence (e.g. ex-Yugoslavia). This paper seeks to explore some of the relations between violence and travel on the example of Dervla Murphy’s traveling through violence.
ENG